Poverty as Malum Simpliciter: A Reading of Aquinas’s Summa contra gentiles 3.133 - Jones, John D. (Philosophy & theology, 2001)
This article provides critical analysis of Aquinas’s designation of poverty as unqualifiedly evil. This paper provides an analysis of two different meanings of poverty: (a) in relation to things or to the external conditions in which people live and (b) in relation to an action in which people engage or are thwarted. Next, the paper discusses the sense in which poverty is an evil—and particularly, an unqualified evil—in relation to both of these meanings of poverty. Since Aquinas claims that poverty is an unqualified evil so far as it prevents people from attaining the ends of sustaining themselves and assisting others, the final section of the paper discusses possible interpretations of these ends, suggesting that each end can be taken in a narrow, minimalist or subsistence sense and a broader, more holistic or contextualized sense.